Clinical Effects of Intensive Insulin Therapy Treating Traumatic Shock Combined with Multiple Organ Dysfunction Syndrome - 杜俊东 刘宏鸣 刘荣 姚咏明 焦华波 赵晓东 尹会男 黎沾良 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
The therapeutic effects of intensive insulin therapy in treatment of traumatic shock combined with multiple organ dysfunction syndrome （MODS） were investigated. A total of 114 patients with traumatic shock combined with MODS were randomly divided into two groups： control group （n=56） treated with conventional therapy, and intensive insulin therapy group （n=58） treated with conventional therapy plus continuous insulin pumping to control the blood glucose level at range of 4.4-6.1 mmol/L. White blood cells （WBC） counts, prothrombin time （PT）, serum creatinine （SCr）, alanine aminotransferase （ALT）, serum albumin and PaO2 were measured before and at the day 1, 3, 5, 7 and 14 after treatment. The incidence of gastrointestinal dysfunction, the incidence of MODS, hospital stay and the mortality were also observed and compared. After intensive insulin therapy, the WBC counts, SCr, ALT and PT were significantly reduced （P0.05）, but the level of serum albumin was significantly increased （P0.05） at the day 3, 5, 7 and 14. In the meantime, the PaO2 was significantly elevated at the day 3, 5 and 7 （P0.01） after intensive insulin therapy. The incidence of gastrointestinal dysfunction, the incidence of MODS, the length of hospital stay and the mortality were markedly decreased （P0.01）. The results suggest early treatment with intensive insulin therapy is effective for traumatic shock combined with MODS and can decrease the length of hospital stay and the mortality.